Isu Kontemporer Legalisasi Ganja untuk Kepentingan Medis dalam Perspektif Hukum Islam - Alfarisyi, M. Tammam; Negara, M. Data Perwira; Yunus, Adrian; Ananda, Bayu; Arso, Dimas Dwi (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This study aims to see the view of Islamic law towards the legalization of marijuana for medical purposes. This type of research is normative research, namely research based on literature (library research). Marijuana is an illegal plant in Indonesia today. This is regulated in law 35 of 2009 concerning Narcotics. The results of this study show that the use of medical marijuana is not allowed in Indonesia. The Constitutional Court (MK) has rejected a lawsuit related to the legality of marijuana for treatment in case decision number 13/PUU-XXII/2024. In Islamic law, marijuana is haram because it contains intoxicating substances and can damage the health of the body and human mind. Scholars agree that anything intoxicating and destructive is haram, based on the postulates of the Qur'an and Hadith. The evaluation of maslahah and mudharat related to the use of marijuana as medicine, from the point of view of Islamic law, emphasizes the urgency of the situation. When the use of marijuana is in an emergency and there is no other alternative to medicine, it can be allowed according to Islamic principles because if marijuana is misused, it will cause mudharat that harms oneself and others.